1965
DOI: 10.1113/jphysiol.1965.sp007577
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium ions on potassium contracture in a locust leg muscle

Abstract: It seems very probable that movement of calcium ions is involved in the excitation-contraction coupling process in vertebrate muscle. The presence of calcium ions in the extracellular fluid appears to be necessary for the production of potassium contractures in vertebrate skeletal (Frank, 1960; Liittgau, 1963), heart (Niedergerke, 1956) and smooth muscle (Edman & Schild, 1962). In contrast to these observations, Hoyle (1961) found that potassium contractures of a locust spiracular muscle were maintained for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1965
1965
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…, Insecta-A large number of early papers describe insect actomyosin isolation, its activation by and hydrolysis of ATP, that its activation requires both Mg ++ and Ca ++ , and the effect of ADP on ATPase activity or muscle fiber tension (Hanson, 1952;Gilmour and Calaby, 1953;Maruyama, 1954bMaruyama, , 1956bMaruyama, , 1957aMaruyama, , 1958bMaruyama, , 1959bMaruyama, , 1966bGilmour and Robinson, 1964;Chaplain et al, 1965;Aidley, 1965;vom Brocke, 1966;Rüegg and Tregear, 1966;Schädler, 1967;Maruyama and Pringle, 1967;Chaplain, 1966aChaplain, ,b, 1967aMaruyama et al, 1968b;Abbott and Mannherz, 1970;Pybus and Tregear, 1972;Griffiths et al, 1979;Wilson and White, 1983;Loxdale and Tregear, 1985). Early work also showed that insect actomyosin is dually regulated Lehman and Szent-Györgyi, 1975;Chantler and Szent-Györgyi, 1978;Sellers et al, 1980).…”
Section: Ecdysozoamentioning
confidence: 99%
“…, Insecta-A large number of early papers describe insect actomyosin isolation, its activation by and hydrolysis of ATP, that its activation requires both Mg ++ and Ca ++ , and the effect of ADP on ATPase activity or muscle fiber tension (Hanson, 1952;Gilmour and Calaby, 1953;Maruyama, 1954bMaruyama, , 1956bMaruyama, , 1957aMaruyama, , 1958bMaruyama, , 1959bMaruyama, , 1966bGilmour and Robinson, 1964;Chaplain et al, 1965;Aidley, 1965;vom Brocke, 1966;Rüegg and Tregear, 1966;Schädler, 1967;Maruyama and Pringle, 1967;Chaplain, 1966aChaplain, ,b, 1967aMaruyama et al, 1968b;Abbott and Mannherz, 1970;Pybus and Tregear, 1972;Griffiths et al, 1979;Wilson and White, 1983;Loxdale and Tregear, 1985). Early work also showed that insect actomyosin is dually regulated Lehman and Szent-Györgyi, 1975;Chantler and Szent-Györgyi, 1978;Sellers et al, 1980).…”
Section: Ecdysozoamentioning
confidence: 99%
“…In a solution made up to contain 6 mms 'Analar' strontium chloride and 2 mM EDTA, which will therefore contain approximately 4 mM strontium ions, it can be calculated that the concentration of ionic calcium will be less than 1 /%M. This is well below the lower limit of calcium-ion concentration necessary for the production of potassium contracture (Aidley, 1965), and is probably rather lower than that of a nominally 'calcium-free' Ringer's solution which does not contain EDTA. Treatment of a muscle, which had previously been depleted of calcium by treatment with EDTA-Ringer, with such a solution produced the usual submaximal phasic contraction on perfusion with KCI solution.…”
Section: Resultsmentioning
confidence: 99%
“…3B of the previous paper (Aidley, 1965), where contraction resulted from the addition of calcium ions to a calciumdepleted muscle in KCI solution. When a muscle has been perfused with EDTA-Ringer for a sufficient time, perfusion with KCI solution no longer results in contraction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations